A holistic risk management framework for renewable energy investments. (May 2022) - Abba, Z.Y.I.; Balta-Ozkan, N.; Hart, P.
Abstract: Private investments are critical enablers to achieving energy access for over 770 million people worldwide. Despite decreasing capital costs, investments in renewable energy (RE) projects in developing countries are low due to unattractive risk-return profiles. Through understanding key risks drivers and their interactions, actionable insights can be drawn to mitigate investment risks, making energy more accessible. This paper reviews RE risks and methods used for risk assessment and mitigation for developed and developing countries with a focus on Sub-Saharan Africa countries (SSA). The review finds that while risk analysis and evaluation mainly employed semi-quantitative multicriteria decision analysis (MCDA) and system dynamics (SD) methods for developing countries, qualitative methods were used to identify mitigations. The methods assessed technical and economic risks at a minimum, while MCDA and SD methods can assess social, political, and policy risks. The efficacies of mitigations were tested using SD and quantitative methods such as agent-based modelling and Monte Carlo simulation. The paper further introduces a 'holistic multi-dimensional investor risk management framework' which can be used to identify actions to improve investment risks in a structured manner. The framework addresses four fundamental limitations observed in the existing literature, recognising that RE risks are complex and involve multidisciplinary perspectives having interactions and feedbacks with other risks, actors, and their actions. This review provides a valuable reference to investors, policymakers, and researchers, providing a catalogue of risks, methods deployed in literature, including a framework to identify impactful actions to improve risk levels. Highlights: Previous review of RE risk management methods has been fragmented. A holistic critical review of risk assessment and mitigation methods is presented. A holistic 'multi-dimensional investor risk management framework' is introduced. The framework addresses four fundamental limitations observed in the existing literature. This framework is further applied from a Sub-Saharan Africa perspective.